The Effect of Tracking Application Systems on Goods Delivery on Customer Decisions - Wulandari, Merry (Jurnal Kesehatan & Disiplin Ilmu, 2024)
Abstract. The purpose of this study is to determine how customer satisfaction is affected by online tracking systems and timely delivery of goods. Data were collected through distributed questionnaires. This study observed J&E customers in Bandung City. The non-probability sample method was used to collect seventy respondents for this study. This study used a quantitative approach. The results of this study indicate that the Online Tracking System (X1) and Timely Goods Delivery (X2) together have a positive and significant influence on customer satisfaction (Y), with a value of 6.018. Timely Goods Delivery (X2) has a positive and significant effect on customer satisfaction (Y), with a value of 9,162. The results of the F test (simultaneous) show that both have a positive and significant effect.